Do credit and training improve fishing income? the case of the fisherfolk in Padre Burgos mariculture zone, Quezon, Philippines - Andres, Jan Marinelle M.; Magistrado, Adolf Miguel L.
This study analyzes the relationship of access to training and credit with the income of mariculture fisherfolk in Padre Burgos, Quezon, Philippines. The data used are based on a survey covering all fisherfolk households in four barangays in Padre Burgos. In the quantile regression, both access to training and credit do not have a significant relationship with fishing income across quantiles. This may be because of the lower capacity of poor fisherfolk to make use of aid that would improve their productivity. Therefore, the variables of interest have weaker effects on their income. However, the signs indicate how income and the variables of interest are possibly related, which tend to vary depending on the level of fishing income. At lower income levels, both credit access and training have a negative relationship with income. This may be explained by the high opportunity costs of time investment and the debt traps experienced by fisherfolk with relatively lower income. At higher quantiles, the relationship of access to training and credit with fishing income becomes positive. This suggests that at higher income levels, the opportunity cost of time investment in training is offset by the expected long-run increase in productivity due to training. In addition, the fisherfolk become less dependent on credit to pay their debt, which allows them to use the loans for fishing investment.